Contribution of Rural Banks to Regional Economic Growth - Devi, Laksmi Yustika (Auckland University of Technology, 2016)
Following the literature on the relationship between financial development, economic growth and the poverty rate, this present study empirically examined the links between rural bank development, economic growth, and the poverty rate at the sub-regional level in Indonesia. The contribution of this research is based on its utilisation of regional variation in rural bank development (over time) to explain the complex relationship between this development and both economic growth and the poverty rate. The first objective of this study was to address the causal relationship between rural bank development and either economic growth or the poverty rate. The second objective was to analyse whether central bank policies or regional government policies on rural banks have had an impact on the development of the banks in Indonesia, and particularly whether the policies have had an impact on the contribution of rural banks to regional economic growth and regional poverty rate reduction. Two methodologies were used in this study. The first methodology was cointegration tests and an error correction based causality test. The second methodology was two stage least squares. The findings of this study were: 1) Cointegration tests indicate that there is a long-run relationship between rural bank assets and regional GDP per capita, and between rural bank assets and the regional poverty rate; 2) DOLS and FMOLS estimations show that rural banks promote economic growth and reduce regional poverty; 3) There is no evidence that rural bank assets Granger-cause regional GDP per capita and the regional poverty rate. The direction of causality is the other way around, from regional GDP per capita to rural bank assets and from the regional poverty rate to rural bank assets; 4) Results of 2SLS estimation show that rural bank assets promote regional economic growth and reduce regional poverty; and 5) The 2SLS estimation also suggests that only one local regulation has a significant effect on the development of rural banks which is local regulation on the development of SMEs. Meanwhile, the national regulations positively and significantly affect rural bank assets, except for developed regions.
Keywords: Rural banks; Economic growth; Poverty; Causality; Two stage least squares